Head and neck surgery - Ferris, Robert L. (LWW, 2013)
V. 1. Larynx, hypopharynx, oropharynx, oral cavity and neck -- v. 2. Thyroid, parathyroid, salivary glands, paranasal sinuses and nasopharynx
Owing to Legal Deposit regulations this resource may only be accessed from within National Library of Scotland. For more information contact enquiriesnls.uk StEdNL
Keywords: Electronic books